1998
DOI: 10.1007/s007050050410
|View full text |Cite
|
Sign up to set email alerts
|

Coinfection of the immunocompromised but not the immunocompetent host by multiple human cytomegalovirus strains

Abstract: Coinfection by multiple human cytomegalovirus (HCMV) strains was investigated in immunocompetent individuals and AIDS patients. Thirty HCMV maternal and fetal or newborn isolate pairs from 9 cases of congenital HCMV infection as well as 36 HCMV isolates and 2 PCR-HCMV-positive CSF samples from 13 AIDS patients were tested by restriction fragment length polymorphism analysis of multiple genome regions. Results from the group of congenital infections showed that: i) all the 9 women with primary HCMV infection pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
23
2

Year Published

2001
2001
2010
2010

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 17 publications
3
23
2
Order By: Relevance
“…Notably, in accordance with this idea, multiple strains were observed to emerge over time in patients who underwent an episode of immunosuppression (3), and the correlation of the presence of multiple strains with high virus load and poor prognosis was observed with immunocompromised adults (11,21,43). Several studies reported a high percentage of adult individuals (3, 49), but not infants (5,50), carrying multiple viral strains. This difference between adult and pediatric patients may also indicate that multiple strains are acquired primarily through consecutive superinfections over time, rather than through a single infection with codisseminating strains, as we see no rationale that could explain why codissemination should affect pediatric patients with lower probability.…”
Section: Discussionsupporting
confidence: 50%
“…Notably, in accordance with this idea, multiple strains were observed to emerge over time in patients who underwent an episode of immunosuppression (3), and the correlation of the presence of multiple strains with high virus load and poor prognosis was observed with immunocompromised adults (11,21,43). Several studies reported a high percentage of adult individuals (3, 49), but not infants (5,50), carrying multiple viral strains. This difference between adult and pediatric patients may also indicate that multiple strains are acquired primarily through consecutive superinfections over time, rather than through a single infection with codisseminating strains, as we see no rationale that could explain why codissemination should affect pediatric patients with lower probability.…”
Section: Discussionsupporting
confidence: 50%
“…This finding is consistent with previous data from analysis of unrelated HCMV strains [Chou, 1990;Baldanti et al, 1998a]. As expected for related HCMV genomes, Toledo-US F and Toledo-UK F showed identical RFLP profiles in each region examined.…”
Section: Restriction Fragment Length Polymorphism and Southern Blot Asupporting
confidence: 93%
“…A single viral strain (identical to that of the mother), however, has been reported in HCMV isolates from congenitally infected newborns [Baldanti et al, 1998a]. The recovery of endothelial cell-tropic viral variants from Toledo, AD169 and Towne strains was assayed in the past, showing that endothelial celltropic variants were apparently present in Toledo virus preparations only [MacCormac and Grundy, 1999]; however, the genomes of the endothelial-cell-tropic variant (Toledo-UK E ) and the parental strain were never compared.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…However, the generation of laboratory strains of WT HCMV is problematic not only because clinical samples often contain multiple strains (27,(29)(30)(31)(32)(33)(34)(35)(36), but especially because genetic adaptations occur even during the early stages of passage in cell culture. Thus, most strains passaged in fibroblasts are mutated in 1 of 3 adjacent genes (UL128, UL130, and UL131A; collectively termed the UL128 locus, UL128L) whose products form a complex bound to glycoproteins gH and gL in the virion envelope (37)(38)(39)(40)(41)(42)(43).…”
Section: Introductionmentioning
confidence: 99%